2005
DOI: 10.1161/circulationaha.104.468397
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1 Levels Are Elevated in Acute Coronary Syndrome

Abstract: Background-Markers of cardiac injury, including troponin-T (TnT), are used to diagnose acute coronary syndrome (ACS); however, markers for plaque instability may be more useful for diagnosing ACS at the earliest stage. Lectin-like oxidized LDL receptor-1 (LOX-1) appears to play crucial roles in the pathogenesis of atherosclerotic plaque rupture and ACS onset. LOX-1 is released in part as soluble LOX-1 (sLOX-1) by proteolytic cleavage. Methods and Results-We examined serum sLOX-1 levels in 521 patients, consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(93 citation statements)
references
References 58 publications
5
88
0
Order By: Relevance
“…In contrast, the role of sLOX‐1 as a biomarker in ischemic heart disease is thoroughly evaluated. Indeed, in CAD, several studies imply that sLOX‐1 has potential as a sensitive biomarker for acute coronary syndrome14, 15, 16, 17, 18 and appears to be significantly higher in acute coronary syndrome than in stable CAD 14, 18. sLOX‐1 is also associated with coronary in‐stent restenosis in patients with stable CAD19 as well as with increased risk of periprocedural myocardial infarction in stable CAD patients undergoing elective percutaneous coronary intervention 20.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the role of sLOX‐1 as a biomarker in ischemic heart disease is thoroughly evaluated. Indeed, in CAD, several studies imply that sLOX‐1 has potential as a sensitive biomarker for acute coronary syndrome14, 15, 16, 17, 18 and appears to be significantly higher in acute coronary syndrome than in stable CAD 14, 18. sLOX‐1 is also associated with coronary in‐stent restenosis in patients with stable CAD19 as well as with increased risk of periprocedural myocardial infarction in stable CAD patients undergoing elective percutaneous coronary intervention 20.…”
Section: Discussionmentioning
confidence: 99%
“…Kita & al demonstrated the important role that oxidized LDLs play in the pathogenesis of atherosclerosis and, as the major endothelial receptor for these; LOX-1 mediates the vast majority of the toxic effects of oxidized LDL [17]. A role of LOX-1 in atherosclerosis is also demonstrated by the fact that this receptor also acts as an adhesion molecule for activated platelets and mononuclear cells [2,18] and could thus promote the recruitment of inflammatory cells and vascular thrombosis. To our knowledge, this study is the only one in our regions to have studied this receptor in sickle-cell anemia, but a preliminary study carried out in our laboratory had found higher levels of LDL oxidized in sickle-cell patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in atherosclerosis, LOX-1 also acts in the inflammatory process. Indeed, recent studies have shown that LOX-1 is involved in the activation of inflammatory processes and inflammation-related disorders [1][2][3][4][5]. Like most surface receptors, LOX-1 can be released in soluble form by proteolytic cleavage and this soluble form (sLOX-1) could be a serum marker in the monitoring of oxidative and/or inflammatory diseases such as sickle-cell disease.…”
Section: Introductionmentioning
confidence: 99%
“…The proinflammatory cytokine IL-18 increased the cleavage of soluble human LOX-1 by 3-4-fold in a concentration-and time-dependent fashion in human embryonic kidney cells transfected with LOX-1 cDNA [96]. Hayashida and colleagues [97] measured soluble LOX-1 in the serum of patients undergoing coronary angiography and found elevated levels in patients with acute coronary syndromes. The increase was observed at an earlier stage of acute coronary syndrome than were other cardiac makers.…”
Section: Lox-1 Protein Structurementioning
confidence: 99%